Social Cognitive Determinants of Dietary Behavior Change in University Employes - Doerksen, Shawna; McAuley, Edward (Frontiers in Public Health, 2014)
Many adults have poor dietary habits and few studies have focused on mechanisms underlying these behaviors. This study examined psychosocial determinants of dietary behavior change in university employees across a 5-month period. Participants completed measures of fruit and vegetable and low-fat food consumption and social cognitive constructs. Multiple regression analyses accounted for a unique proportion of variation in dietary change. Outcome expectations significantly predicted fruit and vegetable and low-fat consumption. Self-efficacy significantly predicted low-fat consumption. Goals were not associated with dietary behaviors. Further research into implementation strategies may provide insight into how goals work to bring about change.